Open letters : Russian popular culture and the picture postcard, 1880-1922 - Rowley, Alison (University of Toronto [Ontario] Press, 2013)
In Open Letters, the most comprehensive study of Russian picture postcards to date, Alison Rowley uses this medium to explore a variety of aspects of Russian popular culture.